The limits of informed consent (Journal of medical ethics, 1975)
The patient, a 59-year-old man, was referred to a psychiatric hospital with what appeared initially to be the signs and symptoms of mental disorder. In hospital a lesion of the brain was diagnosed and surgery was proposed to relieve the condition. The patient, however, during this and subsequent admissions to hospital, refused operation. His refusal to consent was regarded as valid as he seemed to have good insight into his condition. Finally, under section 26 of the Mental Health Act, he was treated surgically. Unfortunately the patient died six weeks later of intracranial haemorrhage. Three comments are made on this case - two by psychiatrists, Dr K Davison and Dr Ashley Robin, the other by a professor of Christian ethics, Professor F C Blackie. Both psychiatrists argue that when a patient's mind is affected by mental or organic illness to the degree that 'he cannot bring a rational and conscious mind' to the question of his treatment then the doctor, in consultation with the relatives, making clear to them the likely course of events if an operation is not performed, must take whatever is the proper course of action, in this case surgery. In this view, such an operation performed immediately the diagnosis was confirmed might not have been so complicated. Professor Blackie, commending 'the attempt to regard the patient as a responsible human being' with a 'moral right to be consulted on all aspects of treatment', questions in this patient the limits to which the appeal to reason was carried. He concludes that 'in this situation the advice and consent of the family must weigh more heavily than the statements of the patient'.